1991
DOI: 10.1901/jaba.1991.24-791
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Stimuli Controlling the Requests of Students With Severe Mental Retardation During a Snack Routine

Abstract: This study assessed stimuli controlling requests during a snack routine after extensive request training with a delayed prompt procedure. During training sessions, one of three three-item snack groups was presented to 3 subjects with severe mental retardation. Assessment sessions involved (a) training conditions (all items were visible), (b) presenting two of three items from a particular group, or (c) presenting no items. One subject requested food items when no food items were present, 2 frequently requested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…Consistent with previous research (i.e., Halle & Holt, 1991;Schussler & Spradlin, 1991), individual differences were found. These results suggest that, even with identical training histories, the stimuli which gain control of requests during intervention may vary across learners.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Consistent with previous research (i.e., Halle & Holt, 1991;Schussler & Spradlin, 1991), individual differences were found. These results suggest that, even with identical training histories, the stimuli which gain control of requests during intervention may vary across learners.…”
Section: Discussionsupporting
confidence: 91%
“…However, it is possible that these delays may have simply provided the opportunity to observe requests at an earlier point in the sequence. Schussler and Spradlin (1991) suggested that control could spread to earlier steps in a sequence when these are reliable precursors to an already effective discriminative stimulus. In their study, the presence of one item from a set of three was viewed as a precursor to the presentation of all three items.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar methods may be applied to hypotheses about other types of communicative behaviors. For example, if the interview and direct observation data suggest that a learner requests preferred food items only when those items are visible, situational probes can be constructed alternating the presence and absence of the foods in the lunch room (Schussler & Spradlin, 1991).…”
Section: Analog Probe Assessmentsmentioning
confidence: 99%